Willingness to pay for improvements in water services in Terengganu, Malaysia : from domestic consumers’ perspectives - Mahirah Kamaludin; Kuna Sandran; A.A. Azlina (Penerbit Universiti Kebangsaan Malaysia, 2018)
Water supply is an expensive investment and it is inevitable that the people have to prepare themselves for a universal hike in water prices in order to secure uninterrupted supply in the future. Inexpensive water prices cause the consumers to take water supply for granted and hence, lack of water conservation initiatives prevail. Sufficient funding is needed to implement various programs to improve water services. The costs of these programs should not be incurred by the water companies which are already burdened by the small revenue resulting from low water price. As the collection of revenue is inadequate to cover operating costs, the services rendered to the consumers are often unsatisfactory and the operational efficiency is below par. The last review of water tariff in Terengganu was done in the last two decades. Hence, with the increase in income within the last two decades, a study is needed to assess consumers’ willingness to pay for improved water services. This study employs Double Bounded Contingent Valuation Method (CVM) to estimate households’ willingness to pay (WTP) for improvements in water services in Terengganu. Monetary benefits of improved water services for the consumers in Terengganu were determined based on the value of WTP. The findings of this study will be used in identifying the frequent problems and issues faced by the government owned water supplier in Terengganu. Efficient water prices will facilitate efforts in delivering better water services and promoting greater efficiency in the financial and operational management of operators to attain financial sustainability.